ENVIRONMENTAL, SOCIAL, GOVERNANCE INVESTING, COVID-19, AND CORPORATE PERFORMANCE IN MUSLIM COUNTRIES - Tekin, Hasan; Güçlü, Fatih (Journal of Islamic Monetary Economics and Finance, 2023)
We examine the impact of Environment, Social, and Governance–ESG investing on corporate performance of non-financial firms in Muslim countries during the pandemic. Employing the random effect panel model with 1,546 firm-year observations, we find that the ESG combined score and its pillars have significant influence on corporate performance during the COVID-19 period. Namely, the performance of firms with higher ESG is relatively less affected as compared to the performance of firms with lower ESG.  We also note that firms in Malaysia and the United Arab Emirates with high ESG have better operational (financial) performance. Finally, from the sectorial perspective, health care and energy (consumer staples) firms with higher ESG have higher operational (financial) performance during the pandemic.AcknowledgmentThe authors would like to thank Bank Indonesia Institute, Bank Indonesia, for the funding that made this study possible.